Pengaruh Penambahan Tepung Kacang Hijau Termodifikasi Annealling Terhadap Karakteristik Fisik, Kimia Dan Organoleptik Roti French Baquette - fitri ponelo; Yoyanda Bait; Lisna Ahmad (Universitas Negeri Gorontalo, 2022)
Green beans are one of the foodstuffs that have good nutritional value because they have the third highest vegetable protein content and can be used as semi-finished products such as flour. The purpose of the study was to determine the effect of the addition of annealing modified mung bean flour on the physical, chemical and organoleptic characteristics of French baquette bread . This study used a single factor Completely Randomized Design (CRD) consisting of 4 treatments (P0 = without the addition of modified mung bean flour, P1 = 10%, P2 = 20% , P3 = 30%). In this study, the sample was repeated 3 times as a validation of the research results. The data was processed using analysis of variance (ANOVA) and the results showed a significant effect on the level so that the test was continued using Duncan Multiple Range Test (DMRT). The results showed that the addition of modified mung bean flour had a significant effect on chemical characteristics of bread and for organoleptic it had no significant effect on (taste and aroma).The value of water content ranges from 26-87% - 33.82%, protein content 9.59% - 14.39%, crude fiber 2.27% - 5.67%, fat content 4.48% - 5.55% , the value of antioxidant activity is 155 – 203 ppm and porosity is 13.99 – 24.75 mm. on organoleptic testing consisting of color with a score of 3.87 – 5.77 (neutral – very like), taste 4.10 – 4.53 (neutral – like), aroma 4.8 – 5.1 (like), texture 3.93 – 5.30 (neutral-like).